HUBUNGAN HIPERTENSI DENGAN GANGGUAN PENDENGARAN SENSORINEURAL PADA PASIEN RAWAT JALAN DI POLIKLINIK TELINGA HIDUNG TENGGOROKAN DI RSUD PROVINSI NTB TAHUN 2014-2017 - Ade Yasinta Dewi; M. Nurman Hikmallah; Sukandriani Utami (Fakultas Kedokteran Universitas Islam Al-Azhar, 2019)
Hearing loss may be conductive hearing loss and sensorineural hearing loss. All cases of hearing loss, 90% are sensorineural hearing loss. The most risk of sensorineural hearing loss are the intensity of noise, age, and history of hypertension disease. Studies show that hypertension causes sensorineural hearing loss. this study is an analytical observational with cross sectional study plan. The sample was covering 96 respondents, consisting of 48 sensorineural hearing loss patients and 48 non-sensorineural hearing loss patients. The study was done using patient medical records at the Ear-Nose-Throat Policlinic of NTB province hospital from 2014 to 2017. Data analysis was performed by contingency coefficient corellation test. The analysis result was significant value p = 0,000 < p (0,05) which showed their significance or correlation of the conducted study. There is a significant correlation between hypertension and sensorineural hearing loss.